KINERJA APARAT DESA DALAM RANGKA OTONOMI DESA DI DESA MANTUIL KECAMATAN MUARA HARUS KABUPATEN TABALONG - Ahmat Harahap (stiatabalong.ac.id, 2019)
The objectives of this study are: 1) To find out and analyze the performance of village officials in the framework of village autonomy at the office of the Mantuil Village in Muara District, Must Tabalong District. 2) To know and analyze any obstacles experienced by village officials in carrying out their duties and authority in Mantuil Village, Muara District, Tabalong District. Data collection techniques in this study are: 1) observation; 2) interview. Interviews are the main instrument, namely with key informants such as village heads, village officials and the community to produce results in the discussion. The results of the study show that the performance of village officials at this time can be said to be good, in the completion of the task performance of village officials it is quite good, only the level of discipline still needs to be improved in order to produce better quality development and for the future to be better The constraints faced are due to lack of good coordination so that there are tasks that are not resolved in time, besides that human resources are less reliable and become an obstacle that causes development to be delayed. Keywords: performance officials of village; autonomy regional